Observations which indicate heterochromatinization of an extra chromosome in the salivary gland cells of Drosophila hybrids - de, H. E M (Springer Nature, 1981)
Salivary gland cells of Drosophila mulleri/D. arizonensis aneuploid male hybrids carrying 3 microchromosomes exhibited morphological features which indicate heterochromatinization of one of the small polytene chromosomes. The process apparently changes the chromosome surface producing a coating with a net-like structure and a strong affinity for lacto-acetic orcein. The possibility of a dosage compensatory mechanism operating to counteract the effect of the extra chromosome is discussed on the basis of previous data which indicated that the microchromosomes of these species have ribosomal cistrons and are controlled by regulatory mechanisms especially evident in hybrids. © 1981 Dr W. Junk Publishers.